Beneficial Effects of Vaccination on Cardiovascular Events: Myocardial Infarction, Stroke, Heart Failure - Fountoulaki, Katerina; Tsiodras, Sotirios; Polyzogopoulou, Eftychia; Olympios, Christophoros; Parissis, John (Cardiology, 2018)
Influenza and pneumococcal infections have been suggested to be potential risk factors for causing adverse cardiovascular events, especially in high-risk patients. Vaccination against respiratory infections in patients with established cardiovascular disease (CVD) could serve as a potential cost-effective intervention to improve their clinical outcomes and cardiac societies have encouraged it. Previous studies have shown that influenza vaccination reduce mortality, acute coronary syndromes and hospitalization in patients with coronary heart disease (CHD) and/or heart failure (HF). However, there is a paucity of randomized prospective clinical trials in the field of the pneumococcal vaccination, and additional higher-quality evidence is needed. Furthermore, questions around the role of vaccination in the primary prevention of CVD, the optimal dose and timing are largely unanswered. The pathophysiologic mechanism in which vaccination provides cardiovascular protection may be related to the modification of the immune-inflammatory model of atherogenesis. The present review summarizes the current evidence and understanding for vaccination against influenza and streptococcus pneumoniae in CHD, HF and stroke and highlights its beneficial effect in the reduction of adverse cardiovascular events.